Practicas de bioseguridad de la enfermera y estancia hospitalaria del neonato de la unidad de cuidados intensivos, Hospital Nacional Ramiro Priale Priale - Huancayo 2011 - Veliz Villanes, Liz Marilyn (2014)
The present research quantitative, descriptive, cross-sectional study Conducted During the months of January to April 2011 at the National Hospital "Ramiro Priale Priale" Huancayo, in order to determine how influences Biosecurity Practices Nurse in hospital stay the neonate in the intensive care unit . The sample universe consisted of the 16 nurses who care Neonatal Provide service in the newborn intensive care unit and who met the inclusion criteria. For data collection checklist was used to determine to biosecurity practices of the nurse in neonatal care and a list of registry to determine the infant's hospital stay by medical records. The information is presented in tables Obtained of single and double entry, statistical test for statistical analysis Pearson correlation was used. The results show no relationship Between the variables and no significant sample. The results Obtained Applied Demonstrate biosecurity practices by the nurse in the care of the baby, 75 percent against 25 percent Applied properly is done improperly. As for the infant's hospital stay in the intensive care unit, 56.3 percent of infants in an acceptable time REMAIN Compared to 43.8 percent unacceptable. By associating the variables, we Observed That is Appropriate biosecurity practices and acceptable hospital stay in 66.7% and 33.3% Biosecurity Measures Implemented properly and hospital stay was still not acceptable.